Association of Bacillus subtilis and Bacillus amyloliquefaciens: minimizes the adverse effects of necrotic enteritis in the gastrointestinal tract and improves zootechnical performance in broiler chickens - Rodrigues, Romário A. [UNESP]; Silva, Leandro A.M. [UNESP]; Brugnera, Heloisa C. [UNESP]; Pereira, Natália [UNESP]; Casagrande, Mariana F. [UNESP]; Makino, Lilian C. [UNESP]; Bragança, Caio R.S.; Schocken-Iturrino, Rubén Pablo [UNESP]; Cardozo, Marita V. (Elsevier, 2024)
This study aimed to evaluate the efficiency and capacity of the probiotic composed of Bacillus subtilis and Bacillus amyloliquefaciens, in improving the zootechnical performance of broiler chickens challenged with Eimeria spp. and Clostridium perfringens. The broilers were distributed in a completely randomized design in poultry isolators (12 birds each), resulting in 3 treatments: T1 (control, no challenge and no Bacillus in diet), T2 (challenged with Eimeria spp., followed by Clostridium perfringens infection and no Bacillus in the diet), and T3 (challenged with Eimeria spp., Clostridium perfringens and treated with Bacillus subtilis and Bacillus amyloliquefaciens). They were evaluated for a period of 29 d, divided into preinitial (1–7 d of age), initial (8–21 d), and growth (22–29 d) phases. Assessments of body weight, weight gain, feed consumption, and feed conversion were conducted, along with the classification of the scores and optical microscopy of the tract gastrointestinal. The animals challenged and treated with the probiotic containing Bacillus spp. showed improved indicators of zootechnical performance. Additionally, the animals challenged and treated (T3) had a better score for intestinal lesions compared to the other treatment groups. Therefore, the probiotic consisting of Bacillus subtilis and Bacillus amyloliquefaciens could be considered an effective option for disease prevention and improving the zootechnical performance of broiler chickens
Keywords: Bacillus spp.; coccidiosis; growth performance; gut function; one health